A titanium alloy implant’s surface characteristics as a result of the sandblasting and shot peening processes - Balasubramanian, K.; Vikram, R.; Samson, C. J.; Arun, B. S. (AIP conference proceedings, 2024)
Titanium alloy, a highly valued implant material, continues to be the subject of research focused on enhancing its surface characteristics. Our study investigates the surface modification of titanium alloy through sandblasting and shot peening techniques, comparing their effects. Parameters such as pressure, distance, and time were kept consistent throughout the experiments. The results reveal that both sandblasting and shot peening effectively modify the alloy’s surface. Analysis included surface roughness, surface-level and sub-surface hardness measurements, along with proposed mechanisms for the observed modifications. Our findings demonstrate significant changes in titanium alloy’s surface characteristics after both treatments. Sandblasting yielded the highest surface roughness at 6.22 µm, while shot peening produced the maximum surface-level hardness of 407.3 VHN.